Preparation method of hydrophobic modified lithium titanium aluminum phosphate powder for diaphragm coating
By performing nano-sand abrasion and silicone resin coating on LATP powder, the problem of high water absorption of LATP materials is solved, and the preparation of hydrophobic modified LATP powder is realized, which reduces manufacturing cost and energy consumption, and is suitable for large-scale Production.
Patent Information
- Application Number
- CN202411292290.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
LATP solid electrolyte materials are limited in their use in the lithium battery field due to their high water absorption. The existing modification methods are complex, costly and unsuitable for large-scale production.
By mixing LATP coarse powder with sand-mill solvent and polymer dispersant in a high-speed dispersion tank, performing nano-sand abrasion treatment, adding silicone resin for low-speed sand-milling coating, and finally obtaining hydrophobically modified LATP powder by spray drying .
It significantly reduces the water content and water absorption rate of LATP powder, simplifies the processing process, saves energy consumption and labor, reduces manufacturing costs, and is suitable for large-scale mass production.
Smart Images

Figure CN119133773A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating. Background Art
[0002] Sodium fast ion conductor (NASCICON) type solid electrolyte lithium aluminum titanium phosphate Li 1+x Al x Ti 2-x (PO4)3 (abbreviated as LATP, where 0≤x≤0.5) is a type of inorganic solid electrolyte that has attracted much attention in recent years. LATP exhibits high ionic conductivity (10-4S / cm) at room temperature, and has low requirements for storage and assembly conditions. Its structural properties are very stable in air and humid environments. At the same time, due to the rich source of raw materials, LATP is also one of the solid electrolytes with the lowest cost and the best commercial prospects. In addition, due to the high ion transfer rate of LATP solid electrolyte, it can not only be used as a solid electrolyte, but also as a positive electrode coating material. In addition, lithium aluminum titanium phosphate can also be used as a coating material in the field of semi-solid battery coating diaphragms. Compared with the traditional inorganic coating materials (alumina, boehmite) on the market, it has the following core competitive advantages: on the basis of traditional inorganic coating materials, it can not only improve the temperature resistance of the diaphragm and the wettability of the electrolyte, but also form a solid-liquid mixed electrolyte to promote the efficient transmission of lithium ions, thereby improving the rate performance of the battery, which is suitable for the needs of fast-charging power batteries in the future. On the other hand, it can provide uniform lithium deposition, inhibit the growth of lithium dendrites, and improve the safety of the battery cell.
[0003] At present, LATP has the characteristics of fast water absorption and high water content, which seriously limits its use in the field of lithium batteries, mainly because there are a large number of hydrophilic groups (-PO4) on the surface of LATP materials. At present, in order to reduce the moisture content of LATP solid electrolytes, higher baking temperatures are usually used to remove moisture. In addition, even if the moisture content of LATP materials is baked to a lower level, it will easily absorb moisture from the surrounding environment during long-term storage and processing. This puts higher requirements on the dew point temperature in different application scenarios, which will inevitably increase the cost of its use.
[0004] Patent CN117832496A coats a layer of hydrophobic material NaSt or NaOL on the surface of LATP to inhibit the water absorption of LATP material. NaSt or NaOL needs to be modified when heated, which is troublesome to operate and complicated. In addition, NaSt or NaOL is an anionic surfactant, and LATP modified by them is prone to generate bubbles when diaphragm coating pulping, which is not conducive to diaphragm coating processing, and anionic surfactants are sensitive to pH values, and LATP modified by them is limited to the pH of pulping for diaphragm coating.
[0005] Patent CN117254205A obtains a preliminarily modified LATP powder material by using a silane coupling agent to fully react with the surface hydroxyl groups of LATP. According to the current test results, there are no obvious hydroxyl groups on the surface of LATP, so it is speculated that the degree of the modification reaction is very low and the effect of hydrophobic modification is not obvious.
[0006] Patent CN117996166A obtains LATP composite solid electrolyte material with in-situ oxygen defect coating layer by multiple coating and sintering. This solid electrolyte has small particle size, excellent structural chemical stability, good hydrophobicity, and multiple applications, but the process is complicated, the process route is cumbersome, the production cost is high, and it is not suitable for large-scale batch production.
[0007] Patent CN117525551A provides a core-shell composite material, including a core, a first coating layer coated on the surface of the core, and a second coating layer coated on the surface of the first coating layer to solve the problem of water absorption in LATP storage. The first coating layer is a surface modifier, and the surface modifier contains a large amount of -COOH, which will inevitably cause the final LATP powder to have strong acidity, limiting its application range. Summary of the invention
[0008] In view of the above problems, the present invention aims to provide a method for preparing hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating.
[0009] To achieve the technical purpose, the scheme of the present invention is: a method for preparing hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating, the specific steps are as follows: S1. Mixing: Add sand milling solvent, polymer dispersant and LATP coarse powder into a high-speed dispersion tank in proportion, stir and mix evenly to obtain a mixed solution; S2, sand milling: the obtained mixed solution is subjected to nano-sand milling treatment by a sand mill to prepare a nano-dispersed solution with uniform particle size distribution; S3, coating: reducing the grinding speed of the sand mill, adding silicone resin to the nano-dispersed liquid for low-speed sand milling. During the low-speed sand milling process, the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion; S4, drying: spray drying the obtained hydrophobically modified LATP dispersion to obtain hydrophobically modified LATP powder after drying.
[0010] Preferably, in step S1, the solid content of the mixed solution is 10%-60%.
[0011] Preferably, in step S1, the LATP coarse powder particles have a LATP particle size D50 of 1-10 μm, and the amount of LATP coarse powder added accounts for 10-60% by mass of the mixed solution.
[0012] Preferably, in step S1, the sand milling solvent is one or more of N-methylpyrrolidone, methanol, ethanol, isopropanol, n-butanol, acetone, DMAC, p-xylene, and mixed xylene, and the amount of the sand milling solvent added is 38-89.9% by mass of the mixed solution; Preferably, the polymer dispersant is one or more of ammonium polyacrylate, sodium polyacrylate, and polyvinyl pyrrolidone, and the amount of the polymer dispersant added is 0.1-2% by mass of the mixed solution.
[0013] Preferably, in step S2, the particle size D50 of LATP in the nano-dispersion liquid is 300-800 nm.
[0014] Preferably, in step S3, the amount of silicone resin added is 0.1-5% of the mass of the LATP coarse powder.
[0015] Preferably, in step S4, the inlet hot air temperature of the spray drying is 130-210° C., and the processing capacity is 5-500 kg / h.
[0016] The method of the present invention has the beneficial effects that it is suitable for preparing LATP nano powder for membrane coating, firstly, the LATP coarse powder is sand-milled to nano-size, and then silicone resin is added to coat the surface of the LATP powder for hydrophobic modification to obtain hydrophobic LATP powder. On the one hand, the use of silicone resin to coat the surface of the LATP nano powder can significantly reduce the water content and water absorption rate of the powder. On the other hand, the processing process of the LATP nano powder is shortened, energy consumption and labor are saved, and the manufacturing cost of the hydrophobically modified LATP is effectively reduced, which is suitable for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The particle size diagram of the LATP powder finally prepared in Examples 1-3 and Comparative Example 1; Figure 2The water drop state diagram of the LATP ceramic sheet of Examples 1-3 and Comparative Example 1; Figure 3 It is the water absorption curve of LATP nanopowder of Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION
[0018] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0019] like Figure 1-3 As shown, the specific embodiment of the present invention is a method for preparing hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating, and the specific steps are as follows: S1. Mixing: Add 38-89.9% by mass of sand milling solvent, 0.1-2% of polymer dispersant, and 10-60% of LATP coarse powder in a high-speed dispersion tank in proportion, stir, and evenly mix to obtain a mixed solution; the solid content of the mixed solution is 10%-60%. The LATP particle size D50 in the LATP coarse powder particles is 1-10μm. The sand milling solvent is one or more of N-methylpyrrolidone, methanol, ethanol, isopropanol, n-butanol, acetone, DMAC, p-xylene, and mixed xylene; the polymer dispersant is one or more of ammonium polyacrylate, sodium polyacrylate, and polyvinyl pyrrolidone; S2. Sand milling: The obtained mixed solution is subjected to nano-sand milling treatment by a sand mill to prepare a nano-dispersion liquid with uniform particle size distribution; the particle size D50 of LATP in the nano-dispersion liquid is 300-800nm.
[0020] S3, coating: reduce the grinding speed of the sand mill, add silicone resin to the nano-dispersion liquid for low-speed sand milling, during which the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion; the total mass of LATP remains unchanged during the sand milling process, and the amount of silicone resin added is 0.1-5% of the total mass of LATP.
[0021] S4, drying: spray drying the obtained hydrophobically modified LATP dispersion to obtain hydrophobically modified LATP powder. The inlet hot air temperature of the spray drying is 130-210°C, and the processing capacity is 5-500kg / h. Example
[0022] This embodiment provides a method for preparing a hydrophobically modified lithium aluminum titanium phosphate powder material, comprising: S101, uniform mixing of LATP coarse powder: 50% ethanol, 1% sodium polyacrylate, and 49% LATP coarse powder were added to a high-speed dispersion tank in order by mass percentage, and stirred at a speed of 800 rpm for 30 min to uniformly mix to obtain a mixed solution; S102. Nano-processing of LATP powder: The obtained mixed solution is subjected to nano-processing by a sand mill at a rotation speed of 2100 rpm, and a nano-processed dispersion having a particle size of D50 = 800 nm and uniform distribution is prepared by sand milling;
[0023] S103, surface coating of LATP powder: reducing the grinding speed of the sand mill to 500 rpm, adding 0.2% (based on the mass of LATP coarse powder) of silicone resin to the obtained nano-dispersion liquid for low-speed sand milling. During the low-speed sand milling process, the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion liquid; S104, drying of hydrophobically modified LATP powder: spray drying the obtained hydrophobically modified LATP dispersion, the inlet hot air temperature of the spray drying is 130° C., and the processing capacity is 50 kg / h. After drying, hydrophobically modified LATP powder is obtained.
[0024] Comparative Example 1 S401, uniform mixing of LATP coarse powder: 50% ethanol, 1% sodium polyacrylate, and 49% LATP coarse powder are added to a high-speed dispersion tank in order by mass percentage, and stirred (the speed is the same as in Example 1), and uniformly mixed to obtain a mixed solution; S402, nano-forming of LATP powder: the obtained mixed solution is subjected to nano-sand-milling treatment by a sand mill (the rotation speed is the same as that of Example 1), and a nano-dispersed solution having a particle size D50=800nm and uniform distribution is prepared by sand-milling;
[0025] S403, drying of LATP powder: spray drying the LATP dispersion obtained in S2, the inlet hot air temperature of the spray drying is 130°C, and the processing capacity is 50kg / h. After drying, LATP powder is obtained. Example
[0026] This embodiment provides a method for preparing a hydrophobically modified lithium aluminum titanium phosphate powder material, comprising: S201, uniform mixing of LATP coarse powder: 50% ethanol, 1% sodium polyacrylate, and 49% LATP coarse powder were added to a high-speed dispersion tank in order by mass percentage, and stirred (speed and time were the same as in Example 1), and uniformly mixed to obtain a mixed solution; S202, nano-forming of LATP powder: the obtained mixed solution is subjected to nano-sand-milling treatment by a sand mill (the rotation speed is the same as that of Example 1), and a nano-dispersed solution having a particle size D50=800 nm and uniform distribution is prepared by sand-milling;
[0027] S203, surface coating of LATP powder: reducing the grinding speed of the sand mill (the speed is the same as that of Example 1), adding 0.5% (based on the mass of LATP coarse powder) of silicone resin to the obtained nano-dispersion liquid for low-speed sand milling. During the low-speed sand milling process, the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion liquid; S204, drying of hydrophobically modified LATP powder: spray drying the obtained hydrophobically modified LATP dispersion, the inlet hot air temperature of the spray drying is 130° C., and the processing capacity is 50 kg / h. After drying, hydrophobically modified LATP powder is obtained. Example
[0028] This embodiment provides a method for preparing a hydrophobically modified lithium aluminum titanium phosphate powder material, comprising: S301, uniform mixing of LATP coarse powder: 50% ethanol, 1% sodium polyacrylate, and 49% LATP coarse powder are added to a high-speed dispersion tank in order by mass percentage and stirred (speed and time are the same as in Example 1), and uniformly mixed to obtain a mixed solution; S302, nano-forming of LATP powder: the obtained mixed solution is subjected to nano-sand-milling treatment by a sand mill (the speed is the same as that of Example 1), and a nano-dispersed solution having a particle size D50 of 800 nm and uniform distribution is prepared by sand-milling; S303, surface coating of LATP powder: reducing the grinding speed of the sand mill (the speed is the same as that of Example 1), adding 2% (based on the mass of LATP coarse powder) of silicone resin to the obtained nano-dispersion liquid for low-speed sand milling. During the low-speed sand milling process, the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion liquid; S304, drying of hydrophobically modified LATP powder: spray drying the obtained hydrophobically modified LATP dispersion, the inlet hot air temperature of the spray drying is 130° C., and the processing capacity is 50 kg / h. After drying, hydrophobically modified LATP powder is obtained.
[0029] Table 1 is the particle size table of LATP powders in Examples 1-3 and Comparative Example 1 Test No. Sample name D10 / μm D50 / μm D90 / μm D99 / μm D100 / μm 1345 Example 1 0.523 0.795 1.249 1.643 1.901 2384 Comparative Example 1 0.520 0.795 1.252 1.644 1.901 1585 Example 2 0.523 0.797 1.254 1.644 1.901 1663 Example 3 0.528 0.797 1.304 1.677 1.903 From the attached Figure 1 As can be seen from Table 1 (the test numbers in Table 1 are Figure 1 ), which are LATP nanopowders prepared in Example 1, Comparative Example 1, Example 2 and Example 3, respectively, and have a uniform particle size distribution, with a D50 of about 800 nm, proving that the addition of silicone resin does not change the particle size of the LATP nanopowder.
[0030] From the attached Figure 2It can be seen that adding silicone resin in different proportions improves the hydrophobic properties of LATP powder, and the higher the addition ratio, the better the effect. Therefore, in the process of preparing LATP nano powder for membrane coating by sand milling and nano-processing of LATP coarse powder, silicone resin is added to the surface of LATP powder for hydrophobic modification to obtain hydrophobic LATP powder. On the one hand, the surface coating of LATP nano powder by silicone resin can significantly reduce the water content and water absorption rate of the powder. On the other hand, the processing process of LATP nano powder is shortened, energy consumption and labor are saved, and the manufacturing cost of hydrophobically modified LATP is effectively reduced, which is suitable for large-scale batch production.
[0031] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any slight modification, equivalent substitution and improvement made to the above embodiment based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating, characterized in that: The specific steps are as follows: S1. Mixing: Add sand milling solvent, polymer dispersant and LATP coarse powder into a high-speed dispersion tank in proportion, stir and mix evenly to obtain a mixed solution; S2, sand milling: the obtained mixed solution is subjected to nano-sand milling treatment by a sand mill to prepare a nano-dispersed solution with uniform particle size distribution; S3, coating: reducing the grinding speed of the sand mill, adding silicone resin to the nano-dispersed liquid for low-speed sand milling. During the low-speed sand milling process, the silicone resin coats the surface of LATP to obtain a hydrophobically modified LATP dispersion; S4, drying: spray drying the obtained hydrophobically modified LATP dispersion to obtain hydrophobically modified LATP powder after drying.
2. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S1, the solid content of the mixed solution is 10%-60%.
3. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S1, the LATP particle size D50 in the LATP coarse powder particles is 1-10 μm, and the amount of LATP coarse powder added accounts for 10-60% of the mass percentage of the mixed solution.
4. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S1, the sand milling solvent is one or more of N-methylpyrrolidone, methanol, ethanol, isopropanol, n-butanol, acetone, DMAC, p-xylene, and mixed xylene, and the added amount of the sand milling solvent accounts for 38-89.9% of the mass percentage of the mixed liquid.
5. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: The polymer dispersant is one or more of ammonium polyacrylate, sodium polyacrylate and polyvinyl pyrrolidone, and the added amount of the polymer dispersant accounts for 0.1-2% of the mass percentage of the mixed liquid.
6. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S2, the particle size D50 of LATP in the nano-dispersion liquid is 300-800 nm.
7. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S3, the amount of silicone resin added is 0.1-5% of the mass of the LATP coarse powder.
8. The method for preparing the hydrophobically modified lithium aluminum titanium phosphate powder for diaphragm coating according to claim 1, characterized in that: In step S4, the inlet hot air temperature of the spray drying is 130-210°C, and the processing capacity is 5-500kg / h.
Citation Information
Cited By
Hydrophobic modified lithium aluminum titanium phosphate solid electrolyte, preparation method thereof and lithium ion battery
CN120015906A
